Study on the antifungal potential of Piper betle methanol extract against Colletotrichum gloeosporioides cutinase - Nhung Nguyen Thi Ai; Hai Nguyen Thi Thanh; Quang Thanh Bui; Vinh Phu Nguyen; Tu Quy Phan (Tạp chí Khoa học Đại học Huế: Khoa học Tự nhiên)
Piper betle methanol extract and its compositional characteristics had been evidenced for their effective inhibitability against rice-blast fungus. In this work, they were subjected for further computational efforts to complete their bio-chemo-pharmacological profile, and broaden their anti-fungal potentiality against Colletotrichum gloeosporioides cutinase presentative (PDB-3DEA). As the results, the most noticeable promising inhibitors particularly regard to 5 (DS -10.8 kcal.mol-1; ground-state energy -499.50 a.u.; dipole moment 2.61 Debye; no toxicity; content 49.90 %) and 6 (DS -10.9 kcal.mol-1; ground-state energy -652.15 a.u.; dipole moment 2.82 Debye; no toxicity; content 13.23 %), given by both their natural contents and predicted properties. The theoretical retrievals would reinforce the antifungal activities of P. betle and be conducive to further efforts to develop a green fungicidal alternative with broad-spectrum and cost-effective pesticidal advantages.